A Childhood Beyond the Noise of Time: Matriarchy and Patriarchy in the Modernist Description of Childhood - Grelz, Karin (Nordlit, 1998)
(…) The feminine features so characteristic of Tsvetaeva’s childhood texts are clearly influenced by these discussions and become much more comprehensible within this context.